Cartografia escolar inclusiva: um quiz como recurso pedagógico para estudantes com TDAH - Silva, Marcio Augusto Paulo da (2024)
In the context of nowadays societies, in an increasingly globalized world, the so-called Digital Information and Communication Technologies (DICTs), have been incorporated into their routines, revolutionizing the way people communicate and interrelate, as well as, changing the way people teach and learn at schools. The DICTs, besides being important digital tools in the modern world, they can be used in different professional fields, they can also be used as a new teaching methodology, facilitating and extending educational horizons even further. So, the purpose of this final research is just not only to make evident the introduction of new technologies into the school environment, but moreover their consolidation to the educational practice, the daily lives and needs of all students. The content covered in this research includes the process of evolution of DICTs in Brazil and their incorporation into education, especially with regard to Specialized Educational Assistance (SEA) at schools. Through the analysis of the theoretical basis of this research, emphasis will be placed on a bibliographical review of contents relating to the area of Geography, Cartography and Special Education, aimming for manufacturing and the latter, using of didactic-pedagogical games through an educational tool called Fazgame (creategames),which allows you to create playful and interactive digital games. Therefore, after analyzing what different authors have reported, it will be possible to conclude that it is not enough that the new technologies be available to students and teachers at schools, but also they are qualified to use them. In brief, this research takes aim for the cognitive and social development of special students from Batista School, in Santa Maria, RS, especially those who were diagnosed with ADHD ( Attention Deficit Hyperactivity Disorder). In addition, it seeks for discovering their levels of learning difficulties, as well as create new methodologies to help them.